2020
DOI: 10.1108/lodj-05-2019-0230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of humble leadership on project success: the mediating role of psychological empowerment and innovative work behavior

Abstract: PurposeThis paper aims to examine the impact of humble leadership on project success. The mediating effects of psychological empowerment and innovative work behavior on the relationship between humble leadership and project success are tested.Design/methodology/approachData were collected from 337 individuals employed in the civil construction sector of Pakistan.FindingsThe results showed that humble leadership is positively related to project success. Furthermore, psychological empowerment and innovative work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(137 citation statements)
references
References 95 publications
7
103
0
Order By: Relevance
“…Frequently, the project team is working autonomously outside the organizational hierarchy. This indicates that psychological empowerment in terms of meaning, competence, self-determination and impact can lead to project success by developing the relevant attitudes, values, problem-solving techniques and interpersonal and group methodologies necessary for the successful delivery of the project (Ali et al, 2020;Khan et al, 2020).…”
Section: The Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently, the project team is working autonomously outside the organizational hierarchy. This indicates that psychological empowerment in terms of meaning, competence, self-determination and impact can lead to project success by developing the relevant attitudes, values, problem-solving techniques and interpersonal and group methodologies necessary for the successful delivery of the project (Ali et al, 2020;Khan et al, 2020).…”
Section: The Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Employees who feel respected and support at the workplace are expected to perform well, especially in a project-based organization (Miao et al, 2020;Shanock and Eisenberger, 2006;Tabassi, 2016). Ali et al (2020) asserted that a humble project manager is likely to provoke followers through psychologically empowering by accepting followers' capability, commitment and acknowledgment of their feedback to achieve the project's objectives.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, employees are secure enough to openly present suggestion to leaders and trust their leaders to notice and act coherently 34 . Humble leadership promotes followers to put on fresh ideas and generate an environment where innovative approaches are encouraged to inspire workers to establish inventive solutions before a suitable method is selected 6 . Furthermore, the humble leader makes their subordinates resilient toward precariousness by teachability and responsiveness to criticism and encourages their team members to attempt new things based on trial and error (Mallén et al, 2019) that stimulate creativity among them the followers 35 .…”
Section: The Mediating Role Of Employee Creativitymentioning
confidence: 99%
“…Furthermore, it means a good chance of projects following as the employee creativity element is appropriately applied. The previous work demonstrated that such an operational application produces a climate where subordinates feel confident, adding to the triumph of the venture 6 .…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation